Combined Associations of Smoking and Bullying Victimization With Binge Drinking Among Adolescents in Beijing, China - Chen, Li; Lu, Ruo-Ran; Duan, Jia-Li; Ma, Jun; Zhu, Guangrong; Song, Yi; Lau, Patrick W. C.; Prochaska, Judith J. (Frontiers in Psychiatry, 2021)
Background: Binge drinking and smoking among adolescents are serious public concerns. However, very few studies have explored the reinforcement of bullying victimization by such behavior. Our study aimed at examining the individual and combined associations of smoking and bullying victimization with binge drinking among adolescents in Beijing, China. Methods: A total of 33,694 students from grades 7 to 12 in Beijing, China were anonymously investigated via the cross-sectional Chinese Youth Risk Behavior Surveillance Survey from April to May 2014. Factors such as sociodemographic variables and indicators of smoking, bullying victimization, and binge drinking were analyzed with multiple logistic regressions, and joint and additive interaction effects were tested. Results: Overall, ever-drinking prevalence was 59.1% (boys: 64.4%; girls: 53.7%). Past 30-day binge drinking was 11.5% (boys: 15.6%; girls: 7.4%) and frequent binge drinking was 2.3% (boys: 3.3%; girls: 1.0%). Past 30-day smoking was 10.7% (boys: 16.4%; girls: 5.0%) and past 30-day bullying victimization was 48.7% (boys: 57.3%; girls: 40.1%). The combined effects of smoking and bullying victimization on occasional binge drinking (OR=6.49, 95%CI=5.60–7.52) and frequent binge drinking (OR=10.32, 95%CI=7.52–14.14) were significant, and the additive interaction effect was significant for current smoking and bullying victimization on frequent binge drinking (OR=10.22, 95%CI=9.43–11.07). The additive interaction effect for current smoking and bullying victimization on frequent binge drinking was significant among boys. Conclusion: Bullying victimization reinforced the association of smoking with frequent binge drinking, especially with findings specific to boys. Programs to prevent smoking or bullying or both may reduce binge drinking among adolescents in China.